FORMULATION OF THE INTERNAL STRESS EQUATIONS OF PINNED PORTAL FRAMES PUTTING AXIAL DEFORMATION INTO CONSIDERATION - V. O., Okonkwo; C. H., Aginam; A. C., Ezeagu (European Scientific Journal, ESJ, 2014)
In this work the internal stress equations for pinned portal frames under different kinds of loading was formulated using the equilibrium method. Unlike similar equations in structural engineering textbooks these equations considered the effect of deformation due to axial forces. This effect was captured in a dimensionless constant s, when s is set to zero, the effect of axial deformation is removed and the equations become the same as what can be obtained in any structural engineering textbook. An investigation into the effect of axial deformation on the internal stresses and its variation with the ratios of second moment of areas of the horizontal and vertical members of the frame ( 𝐼2 𝐼1 􀵗 ) and the ratio of height to length of the portal frame ( ℎ 􀵗𝐿) showed that the effect of axial deformation is appreciable and cannot be neglected in vertically loaded portal frames and in frames subjected to significant horizontally distributed loads.